Incorporating Geriatric Assessment into a Nephrology Clinic: Preliminary Data from Two Models of Care. Issue 10 (5th July 2016) - Hall, Rasheeda K.; Haines, Carol; Gorbatkin, Steven M.; Schlanger, Lynn; Shaban, Hesham; Schell, Jane O.; Gurley, Susan B.; Colón‐Emeric, Cathleen S.; Bowling, C. Barrett
Abstract : Older adults with advanced chronic kidney disease (CKD) experience functional impairment that can complicate CKD management. Failure to recognize functional impairment may put these individuals at risk of further functional decline, nursing home placement, and missed opportunities for timely goals‐of‐care conversations. Routine geriatric assessment could be a useful tool for identifying older adults with CKD who are at risk of functional decline and provide contextual information to guide clinical decision‐making. Two innovative programs were implemented in the Veterans Health Administration that incorporate geriatric assessment into a nephrology visit. In one program, a geriatrician embedded in a nephrology clinic used standardized geriatric assessment tools with individuals with CKD aged 70 and older (Comprehensive Geriatric Assessment for CKD) (CGA‐4‐CKD). In the second program, a nephrology clinic used comprehensive appointments for individuals aged 75 and older to conduct geriatric assessments and CKD care (Renal Silver). Data on 68 veterans who had geriatric assessments through these programs between November 2013 and May 2015 are reported. In CGA‐4‐CKD, difficulty with one or more activities of daily living (ADLs), history of falls, and cognitive impairment were each found in 27.3% of participants. ADL difficulty was found in 65.7%, falls in 28.6%, and cognitive impairment in 51.6% of participants in Renal Silver. Geriatric assessment guided care processes in 45.4% (n = 15) of veterans in the CGA‐4‐CKD program and 37.1% (n = 13) of those in Renal Silver. Findings suggest there is a significant burden of functional impairment in older adults with CKD. Knowledge of this impairment is applicable to CKD management.